Management of Montezuma Quail in Texas: Barriers to Establishing a Hunting Season - Louis A. Harveson (National Quail Symposium Proceedings, 2017)
Montezuma quail (Cyrtonyx montezumae) occur throughout the desert southwest, ranging from Vera Cruz, Mexico to southern Arizona, New Mexico, and western Texas. In Mexico, Montezuma quail are a protected species and in New Mexico and Arizona they are a harvested gamebird. The distribution of Montezuma quail has changed significantly during the past century. Currently Montezuma quail are limited in Texas to the Trans-Pecos with remnant populations in the Edwards Plateau. Although Montezuma quail are classified as a gamebird in Texas, seasons are currently closed. Recently, Texas Parks and Wildlife Department has expressed interest in opening the season on Montezuma Quail. In this manuscript I review and chronicle the sociological and biological barriers associated with opening a hunting season for Montezuma quail in Texas. Sociological barriers include landowner competency and trust in state agencies, a growing voice among nonconsumptive users in Texas, a localized ecotourism industry centered on Montezuma quail, and other cultural factors. Biological barriers include lack of data on Montezuma quail population distribution, trends, and abundance; lack of scientific data relative to habitat management for Montezuma quail; or studies simulating the effects of harvest on Montezuma quail. Prior to implementing a hunting season on Montezuma quail in Texas, resource agencies will need to address the biological and sociological challenges outlined in the manuscript.
Keywords: barriers; biological; Cyrtonyx montezumae; hunting season; Montezuma quail; sociological; Texas; Trans-Pecos